Relative efficacy of minoxidil in combination with other treatments for androgenic alopecia: a network meta-analysis based on randomized controlled trials - Xia, Yinfeng; Chen, Hong; Chen, Yongsong; Chen, Zhiyong (Frontiers in Medicine, 2025)
BackgroundAndrogenetic alopecia is the most prevalent form of progressive hair loss. Minoxidil is widely regarded as a standard treatment for this condition. Consequently, we assessed the effectiveness of minoxidil in combination with other pharmacological agents for the treatment of androgenetic alopecia.MethodsA comprehensive search was conducted across four databases–PubMed, Embase, Web of Science, and Cochrane Library–on December 10, 2024. Eligible studies were selected based on the PICOS framework. Data extraction and synthesis were carried out using a Bayesian network meta-analysis, focusing on mean difference and sample size data. League tables and Surface Under the Cumulative Ranking (SUCRA) values were employed to evaluate the relative efficacy of the interventions.ResultsAmong the 20 study groups analyzed, the combination of platelet-rich plasma and basic fibroblast growth factor with minoxidil demonstrated the highest overall efficacy (SUCRA = 93.06%). This combination resulted in a mean increase in hair density of 35.12 hairs/cm2 compared to the group treated with minoxidil alone. In male subgroups, finasteride combined with minoxidil was the most effective treatment (SUCRA = 80.18%). Among seven combination therapies for females, microneedle with minoxidil proved most effective (SUCRA = 87.18%).ConclusionThis study establishes a clinically actionable hierarchy of minoxidil-based combination therapies, providing evidence-based guidance for dermatologists to optimize androgenetic alopecia management.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024623164, identifier CRD42024623164.